Scientific production in Peruvian university education faculties and schools - Santivañez-Isla, Luis A. (2024)
The study analyzed the scientific production of faculty deans and directors of schools of Education in universities in Peru. Under a quantitative approach, an observational, descriptive and cross-sectional study was carried out, analyzing the scientific production of school directors and deans of the faculty of education in SCOPUS, SCIELO and other databases in the period 2023-2024. The results showed that the directors and deans published at least one article in their professional career regardless of the database, of which 28.9% published at least one article in journals indexed in SCIELO and/or SCOPUS, showing that the production scientific knowledge of faculty deans and school directors of Education in licensed universities in Peru is low. The H index and the number of citations is lower in faculties and schools of education, the most frequent type of article is the original article. For this reason, the importance of the directors of the faculties of education is highlighted as an example and as leaders to implement guidelines and policies that establish a research culture in universities. Key words: Scientific research, Professional school, Peru, University.